The Analysis of Workload, Stress, Motivation, Grit, Work Engagement on Work Life Balance Mediated by Burnout: Analisis Beban Kerja, Stress, Motivasi, Grit, Work Engagement terhadap Work Life Balance di Mediasi Burnout - Priyamita; Efriyani Sumastuti; M.Fadjar Dharmaputra (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the factors of Workload, Stress, Motivation, Grit, Work Engagement on Work Life Balance Mediated by Burnout. This type of research is quantitative, the research population is management students class 2020, 2021, 2022 and 2023 who have worked. This study used probability sampling technique with a sample size of 169 students. The measurements in this study used a Likert scale which was then processed withthe IBM SPSS Statistical Version 27 analysis tool using multiple linear regression analysis.The results of this study indicate that Burnout does not successfully mediate the effect of workload on work life balance. Burnout successfully mediates the effect of work stress onwork life balance. Burnout successfully mediates the effect of work motivation on work life balance. Burnout does not successfully mediate the effect of grit on work life balance. Burnout successfully mediates the effect of Work Engagement on Work Life Balance.